Macleod's clinical diagnosis - Japp, Alan; Robertson, Colin (Colin Ernest); Macleod, John 1915- (Churchill Livingstone/Elsevier, 2013)
Suitable for senior medical students and junior doctors as they attempt to make the difficult transition from mastering basic clinical skills to assessing patients in the real world of clinical medicine, this title presents a manual of clinical assessment that describes how common presenting problems are evaluated in modern clinical practice.